2020
DOI: 10.3390/ma13061329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chip Type on the Properties of Chip–Sawdust Boards Glued with Polymeric Diphenyl Methane Diisocyanate

Abstract: This study investigates the effects of chip type and sawdust percentage on physical and mechanical properties of chip–sawdust boards. The used wood chips varied in linear dimensions and original source. The origin determined the wood quality, which translated into the chips’ linear dimensions. The used materials were chips from sawmill waste processing, aggregate processing of sawmill wood, and chips intended for medium-density boards. The experiment demonstrated that the best boards in terms of mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The course of foaming of the modified PUR foams was characterized on the basis of the times of the successive stages of this process and the maximum foaming temperature. This paper is a continuation of the previous research conducted by the authors concerning the possibility of using by-products from wood processing in order to manufacture materials with improved properties, which are used, e.g., in construction and in the production of interior design elements [30][31][32].…”
Section: Synthesis Of Pur Composite Foamsmentioning
confidence: 86%
See 2 more Smart Citations
“…The course of foaming of the modified PUR foams was characterized on the basis of the times of the successive stages of this process and the maximum foaming temperature. This paper is a continuation of the previous research conducted by the authors concerning the possibility of using by-products from wood processing in order to manufacture materials with improved properties, which are used, e.g., in construction and in the production of interior design elements [30][31][32].…”
Section: Synthesis Of Pur Composite Foamsmentioning
confidence: 86%
“…This paper is a continuation of the previous research conducted by the authors concerning the possibility of using by-products from wood processing in order to manufacture materials with improved properties, which are used, e.g., in construction and in the production of interior design elements [30][31][32].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The experimental fillers made it possible to obtain glulams with high bonding strength and low delamination. Polymeric diphenylmethane diisocynate (pMDI) adhesives have been steadily gaining popularity in wood bonding due to their moisture tolerance and fast cure [24,25]. Polymeric diphenylmethane diisocynate bonds filled with western red cedar bark showed a comparable dry shear strength and improved wet shear strength compared with nonmodified pMDI.…”
Section: Introductionmentioning
confidence: 99%
“…However, little research has been performed on the application of sawdust in the production of building materials [11]. Sawdust-based insulation materials [12], particleboard [13][14][15][16][17][18], cement concrete bricks [19,20], fired clay bricks [21][22][23][24][25][26] and unfired bricks [27][28][29][30][31][32][33][34][35] are some of the developed building materials. Ouattara et al [30] showed that with the incorporation of sawdust (0-25%), the dry density of compressed clay bricks decreased, while the strength increased, for a 15-20% sawdust content.…”
Section: Introductionmentioning
confidence: 99%